292 Case report: recurrent paravaginal aggressive angiomyxoma five years after initial excision and diagnosis. (13th November 2020) - Smith, L; Maguire, P; Ó'Riain, C; Gleeson, N
Abstract : Introduction: Aggressive angiomyxoma is a rare mesenchymal tumour found mainly in the pelvis and perineum of women of reproductive age. Although benign, the tumour is deemed aggressive due to the frequency of local infiltration. The mainstay of treatment is surgical excision. Neoadjuvant use of GNRH analogues to limit tumour growth prior to surgical excision has been reported. Reports suggest a recurrence rate ranging from 30 to 72 percent. Methods: This case describes a 39 year old woman who was re-referred to the gynaecological oncology service with suspected recurrence of paravaginal angiomyxoma, five years after surgery to remove the primary tumour. Results: Preoperative magnetic resonance imaging revealed a paravaginal mass measuring 5 cm x 4.5 cm × 5.5 cm extending from the lower vagina and gradually tapering at the level of the vulva on the left side. Following six months of treatment with GNRH analogue, the mass was excised under general anaesthesia. A multilobular tumour extending from the fat of the left labium to the bladder neck and the ischiorectal fossa was excised. Excision beyond the gross margins of tumour was limited by its proximity to the pubic periosteum and bladder neck. The patient recovered well post operatively. As the bland spindle cell lesional cells were difficult to distinguish from non-lesional soft tissue, HMGA2 staining was used to confirm extension of angiomyxoma to those margins of limited excision. Conclusion: HMGA2 staining can be useful for assessing margins in aggressive angiomyxoma, particularly in the setting of recurrent disease with prior surgical change.